Pembuatan Buku Pedoman Perpustakaan Sebagai Sarana Promosi di Perpustakaan Umum Gunung Bungsu - Irmanella, Sherly; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper focuses on making the library handbook as a means of promotion in the public libraryâ€™s youngest mountain. The purpose of this research is to create a handbook of Gunung Bungsu Public Library (PUGB) for the benefit of PUGB and librarians. Data were collected through documentation study, observation and interviews in the PUGB. The handbook is a guide or reference books in conducting activities in the library. The handbook can be used as a tool to facilitate the public to get information about libraries and library collections since the guidebook contains important information about the library. Collection of data and information in making the handbook conducted by ducumentation and observation. The first step in makingÂ handbook is the collection of data and information. Further preparation of the organizational framework. The conteats of the framework are is: a preface, table of contents, overview, vision, mission, functions and objectives, opening hours, membership, order, plan room, system service, type of service, procedure utilization, regulaion borrowing, lending procedures, the procedure returns, sanctions, classification pf library materials, documents call number, classification collection, browse, catalog description, Wi-Fi, e-mail, and cover. The final step in the handbookÂ is making the cover of the . The handbook cover of the book is designed by using the software CorelDraw X5. Keywords: handbook; library